Analysis of Study Programmes for Future Subject Teachers from the Perspective of the Inclusion of Reading Literacy Elements - Jančič Hegediš, Polona; Licardo, Marta (Bralni vzori 2, 2025)
The purpose of the article is to highlight the importance of analysing study programmes, particularly from the perspective of reading literacy. The analysis includes 27 teacher training study programmes at universities in Ljubljana, Maribor and Primorska. The study programmes for training future Slovenian language teachers are examined. The analysis of these study programmes shows that the first cycle of study programmes includes more content, objectives and competencies related to reading literacy than the second cycle, especially at the University of Maribor. A high proportion of reading literacy elements are also included in social science study programmes (e.g. pedagogy, sociology), but less in natural science study programmes (e.g. technology, educational mathematics and biology). An analysis of all programmes indicates that the expansion of vocabulary and technical terminology is the central component of reading literacy. All components of reading literacy must be systematically and structurally included in all study programmes for future subject teachers, as they are not sufficiently included at present.